The paleomagnetism and geology of north-western Iceland (Dataset) ... - Kristjansson, Leo (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: The paleomagnetism and geology of north-western Iceland ...